Tree species composition of 0.1 ha plot at UiTM Jengka education forest (line 12) - Mahyuddin, Noraini; Ab Jalil, Faza Farhana; Fadzil, Muhammad Faiz; Abd Shukor, Ahmed Faiz; Abdullah, Nik Mohd Izwan (2012)
The study was conducted to determine the tree species composition and density in 0.1 - ha plot at UiTM Jengka Education Forest on the line 12. The forest was determined as a secondary forest. The research was carried out for only one plot with the size 50 m x 20 m. A total of 136 trees with diameter at breast height (dbh) at 5.0 cm and above were recorded. This number of trees represents 53 genus, and 75 species from 32 families. The biggest diameter is Dipterocarpus verrucosus with diameter 56.1 cm. The tree density are illustrates the number of individuals per unit area or unit volume. The result shows that our plot is dominated with the species from Euphorbiaceae it represented 8 genera (15.09%) and 8 species (10.67%), 31 individuals (22.79%), meanwhile the largest genera with the highest number of species is belong to Artocarpus with 5 species (6.67%), and the largest genera with the highest number of individual is Croton with 12 individuals (8.82%). The comparison of estimated number of plant taxa by Turner (1995) with number of plant taxa in study plot was 32 family (11.27%), 53 genera (3.17%), and 75 species (0.92%) compared with Peninsular Malaysia 284, 1674, and 8190 respectively. In addition, Euphorbiaceae is the highest density in our plot with 22.79% or 310 individual/ ha for the family, meanwhile for the genus and species Croton is become the highest density in our with8.82% or 120 individual/ha from the total density.